Biodiversity explained in concept maps and interfaces with environmental education (Research, Society and Development, 2023)
Given the importance of thinking globally and acting locally in favor of conserving life on Earth, the availability and access to information must be made easier for everyone. Recognizing the relevance of images as objects of knowledge and mnemonic aids, the research aims to raise and interpret scientific content on biological diversity and its interfaces with environmental education, focusing on aspects of biodiversity highlighted in concept maps. To assess the extent of the integrative potential of this theme, the content analysis method was used, and the selected publications in the Portuguese language were obtained from easily accessible websites focused on scientific dissemination. The careful searches conducted showed that there are few publications available that met the established criteria. However, the evidence points to trends and emphasizes the importance of further understanding of graphic schemes, fostering interdisciplinary data for teaching and research on sustainable development goals (SDG).